A 3D Mapping Of The Surrounding Object Using Stereo-Vision Technique - Mohd Shah, Hairol Nizam; Sulaiman, Marizan; Ab Rashid, Mohd Zamzuri; Kamis, Zalina; Mohd Ali, Nursabillilah; Mohd Aras, Mohd Shahrieel; Wasbari, Faizil; Omar, Zakarya Ali Ahmed (Medwell Journals, 2017)
-